Romanian agriculture in the context of new cap philosophy - approaches and tendencies - Dusmanescu, Dorel; Jean, Andrei; Milenković, Milinko (Economics of Agriculture, 2010)
The approach of the economic role of agriculture in the new European context, implies understanding into a new vision of the mechanism of functioning of this complex system of activities that do not reduces himself only to the agricultural production and to the agro food industry, generally, but they have major implications for the employment, to the use of natural potential of each economy, especially in shaping the rural society, which has continued to hold a signifcant share in European economies. This paper aims to analyze some aspects in the evolution of the CAP to the Community level and influences that it has on Romanian agriculture.